2011
DOI: 10.1148/radiol.11110069
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Elastic Sphere Processing Enables Reproducible Quantification of Vessel Stenosis at CT and MR Angiography

Abstract: The virtual elastic sphere tool is applicable to CT, dual-energy CT, and MR angiography, and it improves reproducibility and efficiency over that achieved with manual stenosis measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…When combined with high-fat diet (HFD) feeding, this process resulted in advanced stenotic plaques within 6 weeks, as detected by micro-computed tomography (42) and immunostaining (Supplemental Figure 1; supplemental material available online with this article; doi:10.1172/JCI61716DS1). We found that 33 miRs, including miR-155 and miR-147, were increased, and 83 miRs were decreased, in carotid arteries with plaques versus those without ( Figure 1A and Supplemental Tables 1 and 2).…”
Section: Mir Expression Profile In Atherosclerosis and Inflammatory Mmentioning
confidence: 99%
“…When combined with high-fat diet (HFD) feeding, this process resulted in advanced stenotic plaques within 6 weeks, as detected by micro-computed tomography (42) and immunostaining (Supplemental Figure 1; supplemental material available online with this article; doi:10.1172/JCI61716DS1). We found that 33 miRs, including miR-155 and miR-147, were increased, and 83 miRs were decreased, in carotid arteries with plaques versus those without ( Figure 1A and Supplemental Tables 1 and 2).…”
Section: Mir Expression Profile In Atherosclerosis and Inflammatory Mmentioning
confidence: 99%
“…Discrimination of contrast agent and soft tissue was achieved by applying a threshold defined as the mean of contrast agent and soft tissue intensity. The lumen area of the vein was measured with the virtual elastic sphere tool (25) (Fig. 2A).…”
Section: Methodsmentioning
confidence: 99%
“…Image analysis, segmentation of micro-CT data and quantification of carotid artery lumen area were performed with the Imalytics Preclinical Software (Gremse-IT, Aachen, Germany). Discrimination of contrast-enhanced blood and soft tissue was achieved by applying a threshold defined as the mean of blood and muscle intensity [12]. The lumen areas of the LCCA and RCCA were measured with the virtual elastic sphere tool [12].…”
Section: Methodsmentioning
confidence: 99%